2008
DOI: 10.1249/mss.0b013e31815aa2ee
|View full text |Cite
|
Sign up to set email alerts
|

Supramaximal Training and Postexercise Parasympathetic Reactivation in Adolescents

Abstract: HIT was more effective than RS training at improving postexercise parasympathetic function and physical performance. In addition, HRRtau, which was more sensitive to training than HRV indices, seems to be a useful performance-related measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
251
8
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(299 citation statements)
references
References 29 publications
31
251
8
4
Order By: Relevance
“…However, the literature is expanding these assessments to the contexts related to the generation of muscle strength and cardiorespiratory fitness in athletes, because of its ability to monitor the status of physical training [19,21,3,7]. The main findings of the study indicate that the 5VJ test characterized by intermittent high intensity loads, revealed differentiated responses of autonomic activity (LF; HF; LF:HF) regarding continuous protocol of R1, R2 and 60SVJ that verified the resistance explosive strength.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the literature is expanding these assessments to the contexts related to the generation of muscle strength and cardiorespiratory fitness in athletes, because of its ability to monitor the status of physical training [19,21,3,7]. The main findings of the study indicate that the 5VJ test characterized by intermittent high intensity loads, revealed differentiated responses of autonomic activity (LF; HF; LF:HF) regarding continuous protocol of R1, R2 and 60SVJ that verified the resistance explosive strength.…”
Section: Discussionmentioning
confidence: 87%
“…During the execution of VJ intermittent high-intensity exercises, an increase in heart rate and stroke volume is required to meet the metabolic demands of skeletal muscles, thus, a response is triggered by ANS with a vagal withdrawal followed by sympathetic dominance [14]. Immediately after the workout session or during continuous VJ exercises, there is a vagal activity return [19,12,7]. Within this perspective, individuals with a predominant vagal activity may display a higher level of tolerance to muscle fatigue [13,10].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of parasympathetic withdrawal and reactivation has been used to monitor acute 14,25,30 and chronic 31,32,33 adaptations induced by physical training on cardiac autonomic function. Our findings suggest that HRVT and short analysis of r-MSSD (i.e., 60 s) during active recovery on a treadmill can be a good and reliable methods for assessing vagal dynamics during and after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to increased plasma volume, allowing for a greater stretch on the heart and increase stroke volume, or greater parasympathetic nervous system sensitivity (Barak et al, 2011;Lauer, 2011). There are several studies that found improved HRr resulting from regular exercise of subjects (Buchheit et al, 2008;Buchheit et al, 2012;Carroll et al, 2012;Simhaee et al, 2013), and others that have found significant correlations between HRr and VO2max (Barak et al, 2011;Lee & Mendoza, 2012). Considering the majority of participants in this study were of at least average cardiovascular fitness, it is reasonable to assume that these participants had enhanced vagal tone and increased plasma volume allowing for a quicker recovery.…”
Section: Discussionmentioning
confidence: 99%